LATEST DROP IN CIGARETTE-RELATED FIRES AND FIRE DEATHS (1983 (830000) DATA AND TRENDS). (Tufts Archival Research Center, 2007)
Memorandum from Philip S. Schaenman and Alexandra Rex to John Rupp regarding their study done on the rate of cigarette related fires and deaths from fires. States that the study done by the fire commission which showed a 20% increase in deaths due to careless cigarette smoking was grossly wrong and that in fact there has been a significant decrease. Cites many mistakes made by the fire commission's study. Suggests many ways to further reduce the number of fires, yet states that significant improvements have been made already without altering the composition of cigarettes, and thus that is not a necessary step to take.